THE ROLE OF THE DRUGS RESERVE UNIT IN PREVENTION TO REDUCE THE NUMBER OF CASES OF DRUG ABUSE AT JEPARA POLICE RESORT - Allan Kenneth Yohanes (Police Studies Review, 2022)
The writing of this final task is motivated by the large number of drug abuse cases in the Jepara region over the past four years. By prioritizing preventive methods, the Jepara Drug Squad performs a preventive role for the community in Jepara to prevent the emergence of intentions and opportunities in carrying out drug abuse so as to create public security and order, by taking preventive measures. The purpose of this paper is to find out how to implement the prevention of The Jepara Drug Satres and What are the efforts of the Jepara Drug Satres in prevention to reduce the number of cases of drug abuse. As an analysis knife, the author uses several theories and concepts, namely: management theory, effort concept, drug reserse unit concept, drug abuse concept, drug abuse prevention concept. With the research area at Jepara Police Station. This research is carried out with a qualitative approach, using field research types, as well as data collection techniques with observation, interviews, and document studies. The location of the research is in Jepara Regency. The results of the study found that there were several problems in the implementation of active prevention where problems were found at the planning, organizing, implementation and supervision stages. There were also several problems in prevention efforts to reduce the number of cases of drug abuse such as lack of support in the form of budgets and infrastructure and there has been no cooperation with the Community Development Unit. So continuing the results of the discovery of this problem, the author describes the steps for solving the problem. Referring to the stages of planning, organizing, implementing, and supervising the author describes any problems found. As well as solving problems of the factors that influence how the Jepara Drug Investigation Unit carries out its role in prevention.